The Relationship of Breakfast and Hemoglobin Levels in Adolescent Girls at SMP Negeri 1 Tapa - Nur Sabrina Aisya Putri Radjak; Sitti Rahma; Andi Mursyidah (Universitas Muhammadiyah Palu, 2026)
This study aims to determine the relationship between breakfast and hemoglobin levels in adolescent girls in the SMP Negeri 1 Tapa area. This study is a quantitative research with descriptive correlation analysis using a cross sectional approach. Based on the results of a study involving 68 respondents, it shows that most young women have breakfast habits in the adequate category, which is as many as 40 respondents (58.8%). The students who were in the breakfast category were good at 18 respondents (26.5%), while the breakfast category was less than 10 respondents (14.7%). In the examination of hemoglobin levels, it was found that the majority of female students experienced low hemoglobin levels, namely 46 respondents (67.6%). Meanwhile, female students with normal hemoglobin levels amounted to 22 respondents (32.4%). The results of the analysis using the Chi-square test obtained a value of p = 0.047, which shows a significant relationship between breakfast habits and hemoglobin levels in adolescent girls at SMP Negeri 1 Tapa.